contestada

Calculate the average rate of change of function on the interval (a,a+h). simplify your expression.Show all steps.
f(x)=3x+2/2x-1

Calculate the average rate of change of function on the interval aah simplify your expressionShow all steps fx3x22x1 class=

Respuesta :

Answer:

Please check the explanation.

Step-by-step explanation:

Given the function

[tex]f\left(x\right)=\frac{3x+2}{2x-1}[/tex]

at x₁ = a,

[tex]f\left(x_1\right)=f\left(a\right)=\frac{3a+2}{2a-1}[/tex]

at x₂ = a+h,

[tex]f\left(x_2\right)=f\left(a+h\right)=\frac{3\left(a+h\right)+2}{2\left(a+h\right)-1}[/tex]

Using the formula to determine the average rate of change

Average rate = [f(x₂) - f(x₁)] / [ x₂ - x₁]

                      [tex]=\:\frac{\frac{3\left(a+h\right)+2}{2\left(a+h\right)-1}-\frac{3a+2}{2a-1}}{a+h-a}\:\:\:\:\:\:\:[/tex]

as a+h-a = h, so    

                      [tex]=\frac{\frac{3\left(h+a\right)+2}{2\left(h+a\right)-1}-\frac{3a+2}{2a-1}}{h}[/tex]

Thus, the everarge rate of chnage:  [tex]\frac{\frac{3\left(h+a\right)+2}{2\left(h+a\right)-1}-\frac{3a+2}{2a-1}}{h}[/tex]

We can further simplify such as:

[tex]=\frac{\frac{3\left(h+a\right)+2}{2\left(h+a\right)-1}-\frac{3a+2}{2a-1}}{h}[/tex]

[tex]=\frac{-\frac{7h}{\left(2a-1\right)\left(2\left(h+a\right)-1\right)}}{h}[/tex]

[tex]=-\frac{\frac{7h}{\left(2a-1\right)\left(2\left(h+a\right)-1\right)}}{h}[/tex]

[tex]=-\frac{7h}{\left(2a-1\right)\left(2\left(h+a\right)-1\right)h}[/tex]

Cancel the common factor h

[tex]=-\frac{7}{\left(2a-1\right)\left(2\left(h+a\right)-1\right)}[/tex]